Influence of moderate hypoxia on vaccine efficacy against Vibrio anguillarum in Oreochromis niloticus (Nile tilapia). (April 2016) - Gallage, Sanchala; Katagiri, Takayuki; Endo, Makoto; Futami, Kunihiko; Endo, Masato; Maita, Masashi
Abstract: Hypoxia is known as a potential immunomodulator in fish. This study therefore assesses the impact of chronic, moderate hypoxia on vaccine efficacy in Oreochromis niloticus . Serum antibody titer was used as a surrogate marker to detect vaccine efficacy. The fish were acclimatized to either moderate hypoxia (55 ± 5% DO) or normoxia (85 ± 5%DO) and immunized with formalin inactivated Vibrio anguillarum . Significantly, a higher antibody titer was found in normoxic fish than in moderate hypoxia. The normoxic group titer peaked at 14th dpv (days post vaccination) while the moderate hypoxic group peaked at 21st or 28th dpv. The absolute blood lymphocyte counts and serum bactericidal activities against V. anguillarum were significantly higher in normoxic fish. Serum killing of V. anguillarum appeared to be mainly via antibody-dependent classical complement pathway. Furthermore, the first week following vaccination appears critical for antibody production. This view was further supported by results obtained from gene expression assay, where the transcription level of all the detected immune related genes (IgM, IL-1 β, TCR-β, MHC-II β), except B cell activating factor, were significantly suppressed following exposure to moderate hypoxia. The overall results highlight that even though moderate hypoxia is not easily detectable in Oreochromis niloticus, it negatively affects antibody production by suppressing and delaying antibody response, ultimately affecting vaccine efficacy. Highlights: Antibody response in Nile tilapia was reduced and delayed due to moderate hypoxia. Optimum DO at early post vaccination is important for maximum antibody production. Reduced serum bactericidal activity is related to moderate hypoxia. Serum bactericidal activity is via antibody-dependent classical complement pathway.